Pengaruh Dosis Pupuk Organik dan Dolomit terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah - Panut Sahari; Eddy Tri Haryanto; Lutfi Dwi Syahrizal (Agrosains : Jurnal Penelitian Agronomi, 2014)
Peanut productivity has decreased significantly caused by low fertilizer use. This study aimed to obtain optimum combination of dolomite and organic fertilizer in order to get high yield productivity of peanut. This study was conducted in the Field Laboratory of Faculty of Agriculture, Sebelas Maret University. The experiment was conducted by using a Randomized Completely Block Design (RCBD) with two factors, namely dolomite and organic fertilizer. The results showed that there was interaction in the application of dolomite and organic fertilizer on plant growth. The use of 100 kgha-1of dolomite and 10 tons ha-1of organic fertilizer provided higher yield than the other treatments on plant height, number of branches, number of pods per plant and weight of 1000 seeds.